Cross-linking Zr-based metal–organic polyhedra via postsynthetic polymerization. Issue 11 (4th October 2017) - Nam, Dongsik; Huh, Jihyun; Lee, Jiyoung; Kwak, Ja Hun; Jeong, Hu Young; Choi, Kyungmin; Choe, Wonyoung
Abstract : Zr-based MOP cages are cross-linked with flexible organic molecules through a condensation reaction, resulting in a highly crystalline framework. Abstract : Metal organic polyhedra (MOPs) have potential as supramolecular building blocks, but utilizing MOPs for postsynthetic polymerization has not been explored. Although MOPs with flexible organic moieties have been recently reported to target enhanced processability, permanent porosity has not been demonstrated. Here, a novel synthetic strategy involving the cross-linking of MOPs via a covalent bond is demonstrated by exploiting a condensation reaction between the MOP and flexible organic linkers. An amine-functionalized Zr-based MOP is cross-linked with acyl chloride linkers in the crystalline state to form cross-linked MOPs. The condensation reaction results in a cross-linked system without significant changes to the structure of the Zr-based MOP. Such cross-linked MOPs provide a microporous tetrahedral cage based on gas sorption analysis. This cross-linking strategy highlights the potential of MOPs as building blocks and provides access to a new class of porous material.